Compound-specific radiocarbon analysis of plant-wax biomarkers in sediment core GeoB7702-3 - Vera D Meyer; Peter Köhler; Nadine T Smit; Julius S Lipp; Bingbing Wei; Gesine Mollenhauer; Enno Schefuß (PANGAEA, 2025)
This dataset comprises compound-specific radiocarbon data of plant-wax biomarkers (high molecular weight nalkanes and high molecular weight n-alkanoic acids) from marine sediment core GeoB7702-3, recovered from the eastern Mediterranean Sea. The record covers the last 18,000 years. The data was analyzed by Accelerator Mass Spectrometry (AMS) using the MiniCarbonDatingSystem (MICADAS) at the Alfred Wegener Institut, Helmholtz Zentrum für Polar und Meeresforschung, Bremerhaven, Germany (AWI). The radiocarbon data presented in this dataset are corrected for procedure blanks and are reported in the fraction modern carbon (F14C) and ?14C notations. The reservoir age offset between the biomarkers and the atmosphere is given to express the age of the biomarkers at the time of deposition in the marine sediments at the core site.